Safety and Efficacy of Natalizumab as Adjunctive Therapy for People With Drug-Resistant Epilepsy: A Phase 2 Study. (2nd November 2021) - French, Jacqueline A.; Cole, Andrew J.; Faught, Edward; Theodore, William H.; Vezzani, Annamaria; Liow, Kore; Halford, Jonathan J.; Armstrong, Robert; Szaflarski, Jerzy P.; Hubbard, Sarah; Patel, Jagdish; Chen, Kun; et al.
Abstract : Background and Objectives: To explore efficacy/safety of natalizumab, a humanized monoclonal anti–α4-integrin antibody, as adjunctive therapy in adults with drug-resistant focal epilepsy. Methods: Participants with ≥6 seizures during the 6-week baseline period were randomized 1:1 to receive natalizumab 300 mg IV or placebo every 4 weeks for 24 weeks. Primary efficacy outcome was change from baseline in log-transformed seizure frequency, with a predefined threshold for therapeutic success of 31% relative reduction in seizure frequency over the placebo group. Countable seizure types were focal aware with motor signs, focal impaired awareness, and focal to bilateral tonic-clonic. Secondary efficacy endpoints/safety were also assessed. Results: Of 32 and 34 participants dosed in the natalizumab 300 mg and placebo groups, 30 (94%) and 31 (91%) completed the placebo-controlled treatment period, respectively (one participant was randomized to receive natalizumab but not dosed due to IV complications). Estimated relative change in seizure frequency of natalizumab over placebo was −14.4% (95% confidence interval [CI] –46.1%–36.1%; p = 0.51). The proportion of participants with ≥50% reduction from baseline in seizure frequency was 31.3% for natalizumab and 17.6% for placebo (odds ratio 2.09, 95% CI 0.64–6.85; p = 0.22). Adverse events were reported in 24 (75%) and 22 (65%) participants receiving natalizumab vs placebo. Discussion: Although the threshold to demonstrate efficacy was not met, there were no unexpected safety findings and further exploration of possible anti-inflammatory therapies for drug-resistant epilepsy is warranted. Trial Registration Information: The ClinicalTrials.gov registration number is NCT03283371. Classification of Evidence: This study provides Class I evidence that IV natalizumab every 4 weeks, compared to placebo, did not significantly change seizure frequency in adults with drug-resistant epilepsy. The study lacked the precision to exclude an important effect of natalizumab.